2023
DOI: 10.1093/rb/rbad007
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of coverage-mass equation to quantify the corrosion inhomogeneity and examination of medium effects on iron corrosion

Abstract: Metal corrosion is important in the fields of biomedicine as well as construction and transportation etc. While most corrosion occurs inhomogeneously, there is so far no satisfactory parameter to characterize corrosion inhomogeneity. Herein, we employ the Poisson raindrop question to model the corrosion process and derive an equation to relate corrosion coverage and corrosion mass. We also suggest corrosion mass at 50% coverage, termed as half-coverage mass Mcorro50%, as an inhomogeneity parameter to quantify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…SEM is a potent tool to investigate the surface morphology of implants [ 43 , 44 ]. Figure 2 A shows the SEM images of surface morphology of PEEK before and after modification.…”
Section: Resultsmentioning
confidence: 99%
“…SEM is a potent tool to investigate the surface morphology of implants [ 43 , 44 ]. Figure 2 A shows the SEM images of surface morphology of PEEK before and after modification.…”
Section: Resultsmentioning
confidence: 99%
“…The interaction between cells and materials is a fundamental issue in the fields of biomaterials and tissue regeneration. Micropillar arrays provide a unique kind of topological surfaces to regulate cell-material interactions. Cell nuclei undergo severe deformation on micropillar arrays with an appropriate dimension, which influenced cell behaviors . Nuclear deformation can also cause chromatin condensation and chromosome relocalization within the nucleus and alter gene expression of the cells. It has been demonstrated that actomyosin and microtubule may synergistically regulate nuclear deformation and chromatin remodeling, finally modulating gene expression .…”
Section: Discussionmentioning
confidence: 99%
“…Their drug existed in the form of ropivacaine base nanoparticles prior to being encapsulated in the biomacromolecular hydrogel. Among various biomaterials, the PLGA–PEG-PLGA hydrogel distinguishes itself as an intelligent synthetic biomaterial that can respond to the change of temperature and exhibits a sol–gel transition with spontaneous physical gelation upon heating. Ding and Chen et al even loaded an anesthetic drug into a pertinent polymeric aqueous solution with BUP, which was injected near the nerve to achieve local analgesia .…”
Section: Discussionmentioning
confidence: 99%